When Treatment Adherence Matters: Interactions Among Treatment Adherence, Instructional Quality, and Student Characteristics on Reading Outcomes. Issue 2 (6th September 2021) - Capin, Philip; Roberts, Greg; Clemens, Nathan H.; Vaughn, Sharon
ABSTRACT: In this study, we examined the extent to which teachers' treatment adherence, instructional quality, and the interaction of these variables influenced eighth‐grade students' content knowledge and reading comprehension. We examined treatment fidelity for students ( n  = 775) in classes randomly assigned to receive an evidence‐based content area reading program called Promoting Adolescents' Comprehension of Text. Results indicate that teachers' instructional quality was a statistically significant, positive predictor of student content knowledge and reading comprehension performance, whereas teachers' treatment adherence was not. Statistically significant interactions between treatment adherence and instructional quality were present, such that teachers' treatment adherence had a stronger impact on student learning outcomes when their overall instructional quality was low. Moderator analyses also revealed that students' pretest performance and English learner status influenced the effects of treatment adherence and instructional quality on student outcomes. These findings help elucidate the conditions under which Promoting Adolescents' Comprehension of Text leads to improved outcomes, and more broadly, underscore the importance of carefully examining dimensions of treatment fidelity when testing the effects of treatment programs.